Cortisol Function Among Early School-aged Homeless Children - Cutuli, J. J. (2010)
Homelessness represents a context of extreme poverty and risk for child development. This study compared the relative influence of two classes of risk in the context of homelessness. Levels of socioeconomic resource-related risk and negative lifetime events were examined with respect to morning cortisol levels and cortisol response to a set of cognitive tasks. Participants were 66 children between the ages of 4 and 7 years staying in an emergency shelter for families. Adversities largely reflecting family level negative life events predicted higher levels of morning cortisol and differences in initial level and change over the course of the session of cognitive tasks. In contrast, a socioeconomic cumulative risk score was not associated with morning or session-related differences in cortisol.